On the question of studying Tatar variants of the epos about Idegey - Mirgaleev I.M.; Fazlutdinov I.I.; Zakirova I.G. (Золотоордынское обозрение)
The purpose of the study: The work is part of the authors’ research aimed at preparing a collection dedicated to the Tatar versions of the “Idegey”epos. It is aimed at reviewing and systematizing archival and published versions of the Tatar version of the dastan, “Idegey”, introducing unexplored variants into scientific circulation, compiling a complete list of texts, and providing their structural and textual analysis. Research materials: Archival and published versions of the Tatar dastan of “Idegey”. Information from literary and historical sources, along with scientific research, was used. The works of famous folklorists are involved, including studies on the dastan “Idegey” by famous folklorists Nigmat Hakim and Naki Isanbet. The scientific novelty of the study is due to the fact that on the basis of the study of archival materials, a review of all the variants known to us and a comparative analysis of individual episodes and motives were made. Based on the analysis, the changes to which the variants were subjected, the transformation of individual motifs, and all kinds of variations of the latter, the degree of preservation of dastan records from different times was revealed. The results of the study and its scientific novelty: the paper proves that the Tatar versions of the dastan about Idegey and Toktamysh were widely spread among the Tatars of the Volga-Urals, western Siberia, and the Crimea as is evidenced by the wide variability of the works. However, the main part of the variants came to us fragmentarily, in a strongly truncated form, and by the time they were fixed, with the exception of the variants recorded by V.V. Radlov and N. Hakim, the named genre ceased to exist in a living natural form. Despite this, the Tatar versions of the dastan “Idegey”, unlike the other Turkic versions which came through the works of ethnographers and historians, are undoubtedly more extensive and numerous, recorded in the original version or preserved in manuscripts in the Tatar language.